2011
DOI: 10.1002/cncr.26298
|View full text |Cite
|
Sign up to set email alerts
|

IDH1 mutations in grade II astrocytomas are associated with unfavorable progression‐free survival and prolonged postrecurrence survival

Abstract: BACKGROUND:The favorable prognostic impact of mutations in the IDH1 gene is well documented for malignant gliomas; its influence on World Health Organization (WHO) grade II astrocytomas, however, is still under debate. METHODS: A previously published database of 127 predominantly surgically treated patients harboring WHO grade II astrocytomas was revisited. Patients were screened for TP53 mutations (sequencing analysis), IDH1 mutations (pyrosequencing), and MGMT promoter methylation (methylation-specific polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
52
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 35 publications
6
52
0
2
Order By: Relevance
“…In addition, IDH mutation in diffuse astrocytic gliomas correlated with a marked survival benefit that remained even after WHO grade stratification. While this finding is consistent with multiple published reports on WHO II, III, and IV gliomas (5,6,11), other large studies have failed to identify any increase in overall survival associated with IDH mutation specifically in WHO II astrocytomas (39,40). While the precise reasons underlying this discrepancy within the literature are unclear, differences in sample cohorts with regard to histopathologic inclusion/exclusion criteria and patient management may contribute.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, IDH mutation in diffuse astrocytic gliomas correlated with a marked survival benefit that remained even after WHO grade stratification. While this finding is consistent with multiple published reports on WHO II, III, and IV gliomas (5,6,11), other large studies have failed to identify any increase in overall survival associated with IDH mutation specifically in WHO II astrocytomas (39,40). While the precise reasons underlying this discrepancy within the literature are unclear, differences in sample cohorts with regard to histopathologic inclusion/exclusion criteria and patient management may contribute.…”
Section: Discussionsupporting
confidence: 87%
“…For example, mutations of the gene encoding isocitrate dehydrogenase 1 are very common in low-grade astrocytomas, oligodendrogliomas, and secondary glioblastomas but very rare in de novo glioblastoma. 20,21 In addition to mutations of isocitrate dehydrogenase 1, low-grade astrocytomas usually have TP53 mutation, whereas oligodendrogliomas typically show 1p/19q loss. 21 Comparing with advanced MRI techniques and genetic characteristics, the VASARI MRI has its own convenience.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 In addition to mutations of isocitrate dehydrogenase 1, low-grade astrocytomas usually have TP53 mutation, whereas oligodendrogliomas typically show 1p/19q loss. 21 Comparing with advanced MRI techniques and genetic characteristics, the VASARI MRI has its own convenience. Considering the advantages and limitations, we suggest combining advanced MRI and genetic characteristics with VASARI MRI, which could help in better understanding of the tumor behavior and tumor grading.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of IDH mutations in the majority of astrocytomas [2, 7, 21, 25] and concurrent analyses revealed that among AA III WHO2007 the presence of these mutations was associated with a significant better clinical course [6, 17, 23], an observation not observed for A II WHO2007 [1, 20]. Numerous studies indicate the possibility that worse outcome of AA III WHO2007 compared to A II WHO2007 is strongly influenced by the inclusion of cases that indeed molecularly represent glioblastoma (GBM).…”
Section: Introductionmentioning
confidence: 99%